Regeneration status of Albizia lebbeck Benth. in different Forest Types of Uttarakhand, Northern India - Chandra, Anup; Verma, P. K.; Prajapati, S.; Baig, S.; Naithani, H. B. (Current Botany, 2025)
The ability of a species to survive in the community under a range of environmental circumstances depends on its regeneration. This study evaluates the regeneration status of Albizia lebbeck across Uttarakhand’s various forest types. The species was found in five different forest types and the overall regeneration was determined to be ‘Good’. The highest seedling density (900 ha-1) was recorded for West Gangetic Moist Mixed Deciduous Forest, while the lowest (100 ha-1) was observed in the Upper or Himalayan Chir Pine Forest. The highest adult density (70 ha-1) was found in Ban Oak Forest and West Gangetic Moist Mixed Deciduous Forest and the least (20 ha-1) was found in Northern Dry Mixed Deciduous Forest. There was a complete absence of sapling stages in the Northern Dry Mixed Deciduous Forest (5B/C2) and Upper or Himalayan Chir Pine Forest (9/C1b) which indicates disturbances in these regions.